Surgical outcome of brain arteriovenous malformation according to the location, A retrospective study - Sharma, Gopal Raman; Karki, Prasanna; Joshi, Sumit; Paudel, Prakash; Shah, Damber Bikram; Sharma, Apurva (Nepal Journal of Neuroscience, 2023)
Background and Objective: The goal of this study was to analyze the association of brain arteriovenous malformations (AVMs) location and its outcome after microsurgical excision. The relation of outcome using modified Ranklin Scale (mRS) at time of discharge, early and last follow ups with respect to location of AVM.Methods: Demographic data, AVM characteristics, and treatment outcomes were evaluated in 47 bAVMs treated with microsurgery between November 2009 and April 2021. For this series, 47 patients were retrospectively reviewed. The mRS was used to assess functional outcome post-surgery with respect to its locationOutcomes: Forty-seven patients (32% female) and 68% male; average age 33.4 years) with brain AVMs were included in this review. Among the AVMs, the mean size was 5.5cm, 83% with hemorrhage, 63% with deep drainage, mean SM grade is 2.74. The non-eloquent AVM comprised of 25.5%. The most common eloquent location was language (36.2%), followed by sensorimotor (23.4%), visual 8.5% and coordination 6.4%. Motor mapping was done in all cases of brain AVM with sensorimotor eloquence. There was no statically significant difference in the baseline patient and AVM characteristics among different subtypes of eloquence. Favorable outcome (mRS 0-2) was seen on both eloquent (100% in visual) and non-eloquent AVMs. Age and AVM size were significant predictor for good overall outcome in last follow-up.Conclusion: Although the sample size of this study is a limitation, the result of our case series demonstrated excellent surgical outcome for visual eloquence, good outcome in sensorimotor and language eloquence. Coordination eloquence had worse overall outcome.